2008
DOI: 10.1213/ane.0b013e31817e7a59
|View full text |Cite
|
Sign up to set email alerts
|

The Antiallodynic Effect of Neurotropin® Is Mediated via Activation of Descending Pain Inhibitory Systems in Rats with Spinal Nerve Ligation

Abstract: These results suggest that the antiallodynic effect of Neurotropin is mediated via activation of descending pain inhibitory systems, such as the noradrenergic and serotonergic systems, which project from supraspinal sites to the spinal dorsal horn. In addition, activation of inhibitory GABAergic interneurons via 5-HT(3) receptors by serotonin released in the spinal dorsal horn may also be involved in the antiallodynic action of Neurotropin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 29 publications
2
21
2
1
Order By: Relevance
“…Consistent with these views and a recent study (Dogrul et al, 2009), our data showed that blockade of spinal 5-HT 3 receptor function by intrathecal Y25130, a selective 5-HT 3 receptor antagonist, attenuated mechanical and thermal hypersensitivity following L5 SNL in rats. Interestingly, recent studies reported that intrathecal injection of 5-HT 3 receptor antagonists such as CGP35348 (Okazaki et al, 2008) or ondansetron (Peters et al, 2010) had no preventive effects on mechanical allodynia and/or thermal hyperalgesia in a rat with L5/6 SNL, which conflicts with the study with the same drug ondansetron in the same SNL model (Dogrul et al, 2009) and our results. However, we noticed that there were no expected plastic changes of both 5-HT immunoreactive intensity and 5-HT 3 receptor innervation in the lumbar spinal dorsal horn at 14 d after L5/L6 SNL in the study reported by Peters and colleagues (Peters et al, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with these views and a recent study (Dogrul et al, 2009), our data showed that blockade of spinal 5-HT 3 receptor function by intrathecal Y25130, a selective 5-HT 3 receptor antagonist, attenuated mechanical and thermal hypersensitivity following L5 SNL in rats. Interestingly, recent studies reported that intrathecal injection of 5-HT 3 receptor antagonists such as CGP35348 (Okazaki et al, 2008) or ondansetron (Peters et al, 2010) had no preventive effects on mechanical allodynia and/or thermal hyperalgesia in a rat with L5/6 SNL, which conflicts with the study with the same drug ondansetron in the same SNL model (Dogrul et al, 2009) and our results. However, we noticed that there were no expected plastic changes of both 5-HT immunoreactive intensity and 5-HT 3 receptor innervation in the lumbar spinal dorsal horn at 14 d after L5/L6 SNL in the study reported by Peters and colleagues (Peters et al, 2010).…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with these views and a recent study [50], our data showed that blockade of spinal 5-HT 3 receptor function by intrathecal Y25130, a selective 5-HT 3 receptor antagonist, attenuated mechanical and thermal hypersensitivity following L5 SNL in rats. Interestingly, some studies reported that intrathecal injection of 5-HT 3 receptor antagonists such as CGP35348 [51] or ondansetron [52] had no preventive effects on mechanical allodynia and/or thermal hyperalgesia in a rat with L5/6 SNL, which conflicts with the study with the same drug ondansetron in the same SNL model [50] and our results. However, we noticed that there were no expected plastic changes of both 5-HT immunoreactive intensity and 5-HT 3 receptor innervation in the lumbar spinal dorsal horn at 14 d after L5/L6 SNL in the study reported by Peters and colleagues [52].…”
Section: Discussioncontrasting
confidence: 99%
“…Neurotropin is an extract from the inflamed skin of vaccinia virus-inoculated rabbits which has been postulated to act by enhancing descending pain inhibitory systems involving 5-HT3 and noradrenergic alpha2 receptors in spinal dorsal www.futuremedicine.com horn [91,92] and in the locus ceruleus [93]. This compound has been used in Japan for many years to treat various chronic painful conditions, including fibromyalgia.…”
Section: Neurotropinmentioning
confidence: 99%